Kapasitas lokal sebagai strategi penguatan pembangunan ekonomi di Jawa Timur: Budaya mataraman dan koperasi pesantren - Kharisma, Virgie Delawillia; Herdiansyah, Herdis (Institute for Advanced Science, Social, and Sustainable Future, 2024)
This research aims to explore the value of local wisdom in the culture of people in East Java and then analyze its influence on economic development in East Java. The research method uses a qualitative approach in a quantitative part (Concurrent Embedded). The qualitative data collection technique uses interviews with experts supported by literature studies, while the quantitative method uses panel data (38 districts/cities and 2013-2017 data). Data analysis is in the form of Fixed Effect Model (E-GLS) panel regression. The research results show that economic development in East Java can optimize the quality of human resources (IPM), which have intellectual and moral qualities (from Mataraman cultural values). Apart from that, Islamic boarding school cooperatives have also been proven significant at a fundamental level of 0.01 in reducing poverty. However, the quality of cooperatives needs to be of concern to the government regarding members' activeness, skills in managing cooperatives, and other empowerment efforts. Without improving the quality of Islamic boarding school cooperatives, it will impact the increasing rate of inequality in East Java.